2021
DOI: 10.1002/slct.202102985
|View full text |Cite
|
Sign up to set email alerts
|

A Convenient Method for α‐Chlorination of 1,3‐Diketones and β‐Keto Esters with DMSO or Ph2SO/(COCl)2

Abstract: It has been found that the monochlorination of most of 1,3‐diketones and β‐ketoesters under investigation can be achieved using DMSO or Ph2SO/(COCl)2 at −20∼0 °C in moderate to high yields. The 1,3‐diketones, which enol forms are stabilized by an intramolecular hydrogen bond, bulky β‐ketoesters, and α‐monoalkylated 1,3‐dicarbonyls undergo chlorination well with DMSO/(COCl)2, whereas the chlorination of the less bulky β‐ketoesters needs Ph2SO/(COCl)2 instead. The chlorodimethylsulfonium salt or chlorodiphenylsu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…The combined reagent, DMSO/(COCl) 2 , is widely used as an oxidant for the oxidation of alcohols, in which the chlorodimethylsulfonium salt is the key active species [15] . In our recent studies about the application of sulfoxide/oxalyl halide in various transformations, it was found that DMSO/(COCl) 2 is quite versatile and can generate various active species in situ , such as CH 3 SCl, [16–18] HCHO, [19] or act as a source of Cl + [20] . We also established a practical preparation method of methyl methanethiosulfonate using DMSO in the presence of catalytic amount of (COCl) 2 [21] .…”
Section: Introductionmentioning
confidence: 99%
“…The combined reagent, DMSO/(COCl) 2 , is widely used as an oxidant for the oxidation of alcohols, in which the chlorodimethylsulfonium salt is the key active species [15] . In our recent studies about the application of sulfoxide/oxalyl halide in various transformations, it was found that DMSO/(COCl) 2 is quite versatile and can generate various active species in situ , such as CH 3 SCl, [16–18] HCHO, [19] or act as a source of Cl + [20] . We also established a practical preparation method of methyl methanethiosulfonate using DMSO in the presence of catalytic amount of (COCl) 2 [21] .…”
Section: Introductionmentioning
confidence: 99%